Modern Catalytic Systems in the Production of Recyclable Polymers - Shomurodbek, Karimov (American Journal of Biology and Natural Sciences, 2025)
This article explores the development and application of modern catalytic systems in the production of recyclable polymers, which play a crucial role in addressing global environmental challenges and promoting sustainable industrial growth. The study examines the chemical and technological aspects of polymer synthesis, focusing on catalysts that enable efficient polymerization processes with minimal environmental impact. Special attention is given to metal-based, organocatalytic, and enzyme-catalyzed systems that contribute to improving reaction selectivity, reducing energy consumption, and enhancing the recyclability of final polymeric materials. The paper also highlights the significance of green chemistry principles in designing next-generation catalysts that facilitate the production of biodegradable and circular-economy-compatible polymers. Various mechanisms of catalytic reactions are analyzed to determine their influence on polymer structure, molecular weight distribution, and material performance. Comparative studies of traditional and advanced catalytic systems reveal the potential of innovative approaches to improve polymer yield, purity, and sustainability. Furthermore, the article discusses industrial and research examples of recyclable polymers such as polylactic acid (PLA), polyethylene furanoate (PEF), and polycarbonates derived from renewable sources. The integration of advanced catalytic technologies in these production processes demonstrates a promising pathway toward eco-efficient polymer manufacturing. Finally, the study emphasizes the importance of interdisciplinary collaboration between chemists, material scientists, and engineers to create scalable solutions for the polymer industry of the future. In conclusion, modern catalytic systems not only transform the efficiency of polymer synthesis but also provide the scientific foundation for a more sustainable, recyclable, and environmentally responsible materials industry.